TREX1 Mutations in Aicardi–Goutières Syndrome with Congenital Glaucoma (Precision Medicine Communications, 2023)
Aicardi–Goutières syndrome (AGS) is a rare genetic disorder that primarily affects the brain, the skin, and the immune system. It is characterized by a group of symptoms that mimic the effects of a viral infection, leading to inflammation in various tissues. Świerczyńska and colleagues presented a case of a neonate with hypotrophy, microcephaly, frostbite-like skin lesions, thrombocytopenia, elevated liver enzymes, and hepatosplenomegaly and showed that she had ‘three prime repair exonuclease 1’ (TREX1) gene mutations. The genetic investigation found pathogenic mutations, c.490C>T and c.222del (novel mutation) in the TREX1 gene showing AGS type 1 (AGS1). High serum IFN-α levels were also found. Later examination showed multiple ocular abnormalities including intraocular pressure (IOP) of 51 mmHg in the right eye and 49 in the left eye. The patient was diagnosed with congenital glaucoma, and it was managed with trabeculectomy with a basal iridectomy of both eyes, resulting in a reduction and stabilization in the IOP to 12 mmHg in the right eye and 10 mmHg in the left eye without any hypotensive eyedrops. This case report adds to the growing evidence of the involvement of the pathogenic c.490C>T and c.222del mutations in TREX1 in ophthalmic abnormalities. J Pers Med. 2023 Nov 15;13(11):1609.  doi: 10.3390/jpm13111609.